2016
DOI: 10.17235/reed.2016.4557/2016
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition risk questionnaire combined with body composition measurement in malnutrition screening in inflammatory bowel disease

Abstract: The purpose of malnutrition screening is to predict the probability of a worse outcome due to nutritional factors. The Malnutrition Universal Screening Tool (MUST) can be used for screening in inflammatory bowel disease (IBD); however, it does not provide details about body composition. Our aim was to assess the body composition and combine this with the MUST method to screen risk of malnutrition and sarcopenia. A total of 173 IBD outpatients were enrolled in this cross-sectional study. The MUST scale indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 31 publications
(29 reference statements)
3
42
1
1
Order By: Relevance
“…This may vary from only mild alterations in trace elements to severe malnutrition with great weight loss due to the involvement of the gastroin-testinal tract and its effects on food intake and absorption. 4,[22][23][24] Malnutrition is especially common in active UC patients after long-term hospitalization; 11,25 however, few studies have evaluated the nutritional status in patients with UC during remission. 4,12,26,27 Only one trial found a more compromised nutritional status (body weight and BMI) in UC patients during remission than in a control group.…”
Section: Discussionmentioning
confidence: 99%
“…This may vary from only mild alterations in trace elements to severe malnutrition with great weight loss due to the involvement of the gastroin-testinal tract and its effects on food intake and absorption. 4,[22][23][24] Malnutrition is especially common in active UC patients after long-term hospitalization; 11,25 however, few studies have evaluated the nutritional status in patients with UC during remission. 4,12,26,27 Only one trial found a more compromised nutritional status (body weight and BMI) in UC patients during remission than in a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from UC lose nutrition because of the nature of the disease and its related clinical manifestations (1, 2). Approximately 23.4% of patients with UC are malnourished (4). An improved nutritional status results in lower postoperative complication rates, and in some cases can even prevent surgery by reducing the activity of the disease (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Given that many hospitalized CD patients have reduced intake, which results in loss of body weight, the MUST may not be a useful screening tool for CD patients. Furthermore, Csontos et al [24] reported that the MUST did not provide sufficient information to enable selection and follow-up of potentially at-risk CD patients in outpatient care. Recently, Velasco et al [25] used various nutritional screening tools to assess hospitalized patients and found relatively good agreement between the SGA, MUST, and NRS 2002.…”
Section: Discussionmentioning
confidence: 99%